2002
DOI: 10.1007/s00104-001-0367-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospektive Multizenterstudien “Kolon-/Rektumkarzinome” als flächendeckende chirurgische Qualitätssicherung

Abstract: Surgical quality control in the form of prospective multicentre observational studies make possible the analysis of the therapeutic situation of a surgical disease under quality assurance aspects. At the same time, the comprehensive data material available will serve the specific planning of prospective randomized studies. With the aid of the present study, a basis for a thorough and complete evaluation of colorectal carcinoma has been created.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
20

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 14 publications
2
18
0
20
Order By: Relevance
“…Despite advanced age and a high-risk profile of the patient population, general morbidity was low (13.2%) and surgical morbidity (20.4%) acceptable. These data confirm previous observations from individual institutions [2,8,9,10,11,12,14,15,16,17], according to which multimodal perioperative care is safe and feasible for patients undergoing elective colonic surgery compared to data from other multicenter studies from Europe and the United States applying ‘traditional’ perioperative treatment [18,19,20,21]. Our results endorse outcomes from small randomized and controlled studies that demonstrated reduction of postoperative general morbidity with fast-track rehabilitation compared to traditional perioperative care [12].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Despite advanced age and a high-risk profile of the patient population, general morbidity was low (13.2%) and surgical morbidity (20.4%) acceptable. These data confirm previous observations from individual institutions [2,8,9,10,11,12,14,15,16,17], according to which multimodal perioperative care is safe and feasible for patients undergoing elective colonic surgery compared to data from other multicenter studies from Europe and the United States applying ‘traditional’ perioperative treatment [18,19,20,21]. Our results endorse outcomes from small randomized and controlled studies that demonstrated reduction of postoperative general morbidity with fast-track rehabilitation compared to traditional perioperative care [12].…”
Section: Discussionsupporting
confidence: 80%
“…Several forms of bias make a comparison of data from different studies impossible, although it is remarkable that none of the traditional registries yielded general morbidity rates of less than 15%. General complications occurred in 622 (27.1%) of 2,293 WGCRC patients with colonic cancer [21] but only in 13.2% of FTCII patients. Pneumonia and atelectasis were observed in 11.3% of patients with traditional perioperative care (WGCRC colon [21]) but only 4.9% of FTCII patients receiving multimodal therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diese ist als externe Qualitätssicherungsmaßnah-me Bestandteil der chirurgischen Versorgungsforschung und erfasst das gesamte Klinikspektrum. Ziel der Qualitätssiche-rungsstudie ist die Darstellung der Versorgungssituation und die Erforschung von Ursachen qualitativer Defizite als Ausgangspunkt für Maßnahmen, die der Verbesserung der Ergebnisqualität dienen [1][2][3]. Zahlreiche klinische Studien konnten die Einflussfaktoren «Chirurg» und «versorgende Klinik» als unabhängige Prognosefaktoren für das Outcome (Ergebnisqualität) nach kurativer Tumorresektion beim Rektumkarzinom ausweisen und dabei eine Korrelation zur Fallzahl für den einzelnen Chirurgen (surgeon volume) und die Klinik (hospital volume) herstellen [4].…”
Section: Introductionunclassified